Illicit Financial Flows in Zambia's Integrated Economy: Analysing the effects of illegal taxation practices in the extractives industry on value addition - Mulenga, Mwaba Chileya (Department of Private Law, 2023)
Mining is an important sector of Zambia's economy. Using the Constitution, legislative measures, and other policy pronouncements, efforts are being made by the Zambian government to maximise opportunities for diversification and value addition from mining to other sectors of the economy. Opportunities have been identified mainly in the form of employment creation, skills development, increased production using local goods and services, and integration into the mining value chain. Traditionally, Zambia's mining industry has been dominated by foreign multinational companies since the early 1900s. Therefore, multinational companies as major capital investors are key actors that anchor other service providers in the mining value chain. Their involvement therefore largely contributes to, and in some instances detracts from, the success of these measures to maximise value addition. This research explores the interaction of these companies and other local Zambian businesses in the light of the country's goals for industrialisation and diversification in an integrated multi-sector economy. By analysing the overall legal and economic context in which multinational companies operate, this research demonstrates that illegal tax practices by multinational companies have discernible adverse effects on revenue where funds are syphoned out of the economy illicitly. Also, this research evaluates the multi-dimensional effects of these practices and emphasises that value addition efforts throughout the mining value chain are particularly adversely impacted. The research identifies and critiques inadequacies in the law that fail to address the resultant challenges for local businesses such as lost opportunities for funding and capacity.